2022
DOI: 10.14740/jh989
|View full text |Cite
|
Sign up to set email alerts
|

Iron Deficiency Anemia: An Overlooked Complication of Crohn’s Disease

Abstract: Background There are few studies to evaluate the association between iron deficiency anemia (IDA) and Crohn’s disease (CD). We examined this association in a USA-based cohort of patients with CD. Methods We queried the Nationwide Readmission Databases 2018 using the International Classification of Disease, 10th Revision, and Clinical Modification (ICD-10-CM) codes to identify all adult patients admitted with a diagnosis of CD. Primary outcomes were the prevalence of IDA… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2
2

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 30 publications
(34 reference statements)
1
2
0
Order By: Relevance
“…In the univariable and multivariable MR study, we systematically assessed the iron de ciency anemia with type 2 diabetes, ulcerative colitis and Crohn's disease risk. Consistent with previous research results 5,[9][10][11]28 , our ndings demonstrated a signi cant positive association between IDA and an increased risk of both T2DM and CD. Furthermore, our multivariable MR analysis substantiated a direct causal relationship between T2DM and IDA, while accounting for the confounding effects of other related diseases.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…In the univariable and multivariable MR study, we systematically assessed the iron de ciency anemia with type 2 diabetes, ulcerative colitis and Crohn's disease risk. Consistent with previous research results 5,[9][10][11]28 , our ndings demonstrated a signi cant positive association between IDA and an increased risk of both T2DM and CD. Furthermore, our multivariable MR analysis substantiated a direct causal relationship between T2DM and IDA, while accounting for the confounding effects of other related diseases.…”
Section: Discussionsupporting
confidence: 92%
“…IDA poses a signi cant burden among patients hospitalized for Crohn's disease, as shown by a large cohort study conducted in the United States 5 ; another observational study focusing on patients with in ammatory bowel disease (IBD) revealed that approximately one-fth of the cohort experienced anemia primarily due to ID 6 ; recent guidelines from the European Crohn's Disease and Colitis Organization underline the importance of regular screening and prompt treatment for IDA in individuals with IBD 7 ; a recent study reported varying prevalence rates of ID in hospitalized IBD patients, ranging from 13-90%, with an average of 23% 8 . In the context of type 2 diabetes mellitus (T2DM), a retrospective study involving 1,137 patients found that 39.3% had ID, with ID being most prevalent (61.7%) among those with a duration of diabetes less than 5 years 9 ; another study demonstrated an association between IDA and elevated glycosylated hemoglobin concentrations, which signi cantly declined following iron treatment 10 .…”
Section: Introductionmentioning
confidence: 99%
“…Conversely, clusters 2 and 3 were hardly significantly enriched for medical complaints leading up to their first CD diagnosis (Figure 7B). However, the patients in clusters 2 and 3 did appear to progress more rapidly as evident from developing serious complications after CD onset, including complications due to abdominal pain, nausea, vomiting and iron deficiency anemia [26][27][28] (Figure 7B). Interestingly, although patients in clusters 1 and 4 generally had a better prognosis than patients in clusters 2 and 3, the diagnosis trajectories between clusters 1 and 4 did seem to be quite distinct (Figure S6).…”
Section: Applicationmentioning
confidence: 99%